IMPLEMENTATION OF CIRCULAR ECONOMY IN HEALTHCARE SECTOR FOR APPROPRIATE SUPPLIER SELECTION FRAMEWORK - Kalra, Aayushi; Khurana, Anil; Bali, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The supplier selection framework is the most interested and required objective for the management healthcare area for buying the proper products and to find the best supplier. Hence for finding the finest supplier, the novel technique known as a Hyena Sequence Selection Network (HSSN) was built with the needed sufficient forecasting features. Initially, the suppliers with the circular economy data were collected from the web source and imported into the Python environment. Henceforth, the novel HSSN is built and the prime processes like pre-processing, feature extraction, weighing and supplier ranking scenario were performed. Based on the criterion score, the total weight score was measured and ranks were provided. At the last, the performance score was evaluated in three categories that are accuracy, error rate and computational complexity. In that, the novel HSSN scored the highest accuracy at 96% with the lowest error rate at 4%. It is quite better than the compared traditional models.